RATIONAL USE OF PERSONAL PROTECTIVE EQUIPMENT – COVID 19 PANDEMIC - Abbas, Beenish; Rehman, Abdul; Abbas, Sana; Khan, Faisal Nawaz (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate coherence with reasonable and judicious use of personal protective equipment.Study Design: Cross-sectional study.Place and Duration of Study: Tertiatry Care Hospital, from Feb 2020 to May 2020.Methodology: Methodology constituted of a paper-based and web-based questionnaire based on relevant studies and World Health Organization (WHO) Guidelines. A pilot study carried out at 15-20 participants for questionnaire validation and reviewed by independent experts for face validity, a final questionnaire comprised of 13 multiple-choice questions in addition to information on demographic profile and professional overview. The minimum sample size required for the study was 573, where the prevalence of knowledge of use of personal protective equipment by doctors was considered to be 31.5%.Results: A total of 640 participants enrolled in the study and data extracted from their responses. Age range 24-61 years of sample was with mean age was 36.66 ± 9.0 years. One hundred and sixty (25%) participants were males whereas 480 (75%) were females. Three hundred and four (47.5%) had adequate knowledge about disease transmission and 592 (92.5%) were aware of preventive measures. Five hundred and forty four (65%) declared that N95 to be used in routine patient care, therefore, exhibiting injudicious use. Only 56 (8.8%) were compliant with the length of duration of Respirator use.Conclusion: Due to global mismatch and disruption in the supply chain of Personal Protective Equipment an intricate balance between the safety of healthcare workers, prevention of disease transmission and economic burden to be maintained with adherence to World Health Organization PPE use guidelines.